Perubahan Mutu Fisik, Kimia dan Organoleptik Cabai Blok dengan Variasi Kemasan dan Suhu Penyimpanan - Dwi Anggraini; Faisal Basyir; Kevin Tanjung; Nurul Al Varqani (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This study aims to investigate the impact of packaging type and storage temperature on the physical, chemical, and sensory properties of chili blocks during storage. Additionally, the study aims to identify the optimal packaging and storage temperature combination, as well as to characterize the quality attributes of chili blocks. The experimental design employed was a Completely Randomized Design (CRD) in a factorial arrangement with two factors: packaging type and storage temperature. In this study, using aluminum foil as primary packaging, PP plastic packaging, and paper as secondary packaging, and 3 treatment storage temperatures, each repeated as many as 3 trials, so that it has 18 experimental units. Data analysis using ANOVA with Duncan's Multiple Range Test (DMRT)at a significant level of 5% using the SPSS18 program. The results showed that secondary packaging types and storage temperatures did not significantly affect physical properties (moisture content) and organoleptic properties (color, aroma, texture), but significantly affected the chemical properties (pH, vitamin C, ash content) and secondary packaging types the good for chili block is alufo + plastic packaging and refrigerator storage temperature (10oC), and good chili block characteristics are: Refrigerator storage (temperature 10oC) with alufo + plastic packaging: lowest physical properties (moisture content) 27.29, chemical properties (lowest pH 5.23, Vitamin C 12.91 and ash content 6.35).